Dose intercomparison at Italian hadrontherapy centers. (December 2019) - Guida, F.; Barbato, A.; Ciocca, M.; Schwarz, M.; Lorentini, S.; Mastella, E.; Cirrone, G.A.P.; Petringa, G.; Liotta, M.; Tarabelli De Fatis, P.; Masi, M.; Mettivier, G.; et al.
Highlights: Dosimetric intercomparison for proton beams using ionization chambers and according to the IAEA TRS-398 code of practice. Measurement sites include CNAO (Pavia), CTP (Trento) and CATANA (Catania) Results agree within the 1.5% difference considered acceptable for national dose intercomparison. Abstract: Purpose: To perform the first dosimetric intercomparison for proton beams in Italy using ionization chambers, according to the IAEA TRS-398 code of practice. Methods: Measurement sites included: National Center for Oncological Hadron Therapy (CNAO, Pavia), Center for Proton Therapy (CTP, Trento) and Center for Hadron Therapy and for advanced Nuclear Applications (CATANA, Catania). For comparison we also included a 6 MV photon beam produced at Istituti Clinici Scientifici Maugeri (ICSM, Pavia). For proton beams, both single pseudo-monoenergetic layers (in order to obtain a planned dose of 2 Gy at the reference depth of 2 cm in a water phantom) and Spread-out Bragg peaks (SOBP) have been delivered. Measurements were performed with a PTW Farmer 30010-1 and a PTW Advanced Markus type 34, 045 ionization chamber. Results: Data obtained at CATANA, CNAO and CPT in terms of absorbed dose to water depth show good consistency within the experimental uncertainties, with a weighted mean of 1.99 ± 0.01 Gy and a standard error of 0.003 Gy, with reference to a nominal dose of 2 Gy as designed by the treatment planning system. Conclusions: The results showed a standard deviation of less than 1% for single layer and SOBP beams, for all chambers and a percent deviation less than 1.5% for single layer measurements. The weighted means of the absorbed doses for clinical proton beams (118.19 MeV and 173.61 MeV) are consistent within less than 1%. These results agree within the 1.5% difference considered acceptable for national dose intercomparison.